Contents and assessment of basic tourism resources - Knežević, Rade (Array, 2008)
Summary: The article looks at the attractive factors of basic tourism resources and the structure of their attractions. The general term 'resource' refers to both natural and anthropogenic resources, while the content of this concept refers to elements used in creating a tourism product. Basic tourism resources are the most important factors of tourism processes, with a vital attribute of direct and indirect tourism resources being their substitutability. Natural (biotropic) resources are considered the guiding factors of a tourism offering, and they command great attention when planning tourism development and designing a tourism product. In addition to the basic types of natural tourism resources (geomorphologic, climate, hydrographic, bio-geographical, protected natural heritage), there are also many sub-types. Anthropogenic (atropic) tourism resources are human creations, the features of which attract tourists. They impact on how the cultural needs of tourists are met. In a tourism product, they generally take the form of cultural goods and ethno-social, artistic and ambient resources. Today, potential tourism resources are the focus of research, together with existing tourism resources, the contents and importance of which change and grow over time